Knowledge, attitude and practice of research ethics among dental professionals in dental colleges of South Kerala-A pilot study - Ravindran, Rathy; devi, Harish Rajendran Nair Kandhimadhi (Journal of Orofacial Research, 2020)
Background: Research in the field of dentistry is increasing but there is dearth of information investigating the knowledge, attitude and practice of dental professionals for ethical principles in research especially in developing countries like India. The outcome of the present study will help the institution to understand how well research ethics are accepted in their institution. Methods: A cross sectional survey using validated questionnaire was administered to faculty members and postgraduates of two dental colleges in south Kerala. The questionnaire was designed to take approximately 10 minutes to complete and participants were asked to return it in drop box provided at principal’s office. Results: A total of 97/113 dental professionals participated in the study with a response rate of 86%. Based on the questionnaire, there was fair knowledge among the faculties and postgraduates regarding informed consent, research involving children and research on retrospective samples. Less than one fourth of results showed good attitude towards research ethics whereas more than three fourth participants showed moderate attitude. There was no statistically significant difference between faculty and postgraduates on comparison of attitude towards research ethics (p